STRATEGI MANAJERIAL KEPALA SEKOLAH UNTUK MENINGKATKAN KUALITAS LAYANAN EKSTRAKURIKULER KARATE - Rimang Andani; Rudi Hariawan; Hardiansyah Hardiansyah (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT Extracurricular activities are an important component of educational programs that contribute to the development of students’ potential, skills, and character beyond formal classroom learning. However, the quality of extracurricular services in schools often faces various managerial challenges, including limited facilities, program coordination, and stakeholder involvement. This study aims to examine the principal’s managerial strategies in improving the quality of karate extracurricular services at SMP Negeri 4 Kuripan. This research employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with the principal, vice principal, extracurricular supervisors, and students, as well as document analysis. The findings indicate that the improvement of service quality is achieved through four systematic stages: program identification, provision of facilities, active communication with parents, and resolution of operational constraints, supported by regular evaluations and a gradual sanction mechanism. The strategy for managing parental involvement is implemented by integrating the POAC management functions (Planning, Organizing, Actuating, and Controlling) supported by effective communication. The main challenges identified include scheduling conflicts, limited facilities and infrastructure, and students’ motivation. It can be concluded that the success of the karate extracurricular program depends on a well-structured internal management system, strategic partnerships with parents, and the school’s ability to adaptively address operational challenges in order to create a holistic supporting ecosystem. ABSTRAK Kegiatan ekstrakurikuler merupakan bagian penting dari program pendidikan yang berperan dalam mengembangkan potensi, keterampilan, serta karakter peserta didik di luar pembelajaran formal. Namun, kualitas layanan ekstrakurikuler di sekolah sering menghadapi berbagai tantangan manajerial, seperti keterbatasan sarana, koordinasi program, dan keterlibatan pemangku kepentingan. Penelitian ini bertujuan untuk mengkaji strategi manajerial kepala sekolah dalam meningkatkan kualitas layanan ekstrakurikuler karate di SMP Negeri 4 Kuripan. Menggunakan pendekatan kualitatif dengan desain studi kasus, data dikumpulkan melalui observasi partisipatif, wawancara mendalam dengan kepala sekolah, wakil kepala sekolah, guru pembina, dan peserta, serta studi dokumentasi. Hasil penelitian menunjukkan bahwa peningkatan kualitas layanan dicapai melalui penerapan empat tahap sistematis: identifikasi program, penyediaan sarana, komunikasi aktif dengan orang tua, dan penyelesaian kendala operasional, yang dilengkapi dengan evaluasi rutin dan mekanisme sanksi bertahap. Strategi pengelolaan keterlibatan orang tua diimplementasikan dengan mengintegrasikan fungsi manajemen POAC (Planning, Organizing, Actuating, Controlling) yang didukung komunikasi efektif. Kendala utama yang dihadapi meliputi penjadwalan, keterbatasan sarana-prasarana, dan motivasi siswa. Disimpulkan bahwa keberhasilan program ekstrakurikuler karate bergantung pada struktur manajemen internal yang baik, kemitraan strategis dengan orang tua, dan kemampuan sekolah dalam mengatasi tantangan operasional secara adaptif untuk menciptakan ekosistem pendukung yang holistik.